2021
DOI: 10.12703/r/10-58
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the role of excitation–inhibition balance in motor recovery post-stroke

Abstract: Stroke affects millions of people worldwide each year, and stroke survivors are often left with motor deficits. Current therapies to improve these functional deficits are limited, making it a priority to better understand the pathophysiology of stroke recovery and find novel adjuvant options. The excitation–inhibition balance undergoes significant changes post-stroke, and the inhibitory neurotransmitter γ-aminobutyric acid (GABA) appears to play an important role in stroke recovery. In this review, we summaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 84 publications
2
12
0
Order By: Relevance
“…However, not all the groups showed the showed the bene cial role in functional recovery. The signi cant motor recovery was only shown in PV-ChR2 group There have been many trials to measure the GABA level with controversial results 55 . We found that two types of GABA exist in PV-ChR2 group; GABA released from reactive astrocyte after Wallerian degeneration in the cortex and neuronal GABA released from PV-expressing neurons in capsular infarct model 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, not all the groups showed the showed the bene cial role in functional recovery. The signi cant motor recovery was only shown in PV-ChR2 group There have been many trials to measure the GABA level with controversial results 55 . We found that two types of GABA exist in PV-ChR2 group; GABA released from reactive astrocyte after Wallerian degeneration in the cortex and neuronal GABA released from PV-expressing neurons in capsular infarct model 21 .…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Alternatively, pharmacological agents to modify E/I ratio are available. 43 Therefore, in future stroke, rehabilitation studies spectral exponents could serve as a novel biomarker to identify individuals that might profit from a targeted therapy and simultaneously monitor the effect of such an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Commensurate with decreased inhibitory drive in epilepsy, there is an increase in glutamate-receptor mediated excitability, in part due to alterations in α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) and N-methyl-Daspartate receptor (NMDAR) subunits expression, with increases in the ratios of GluA1/GluA2 AMPAR subunits and GluN2B/GluN2A NMDAR subunits resulting in GluA2-lacking, Ca 2+permeable AMPAR [26][27][28] and extended decay times and elevated Ca 2+ influx, respectively [29][30][31] . Pathologic E:I alterations are not unique to epilepsy, as evidence for neuronal hyperexcitability has been seen in other neurodevelopmental and neurodegenerative disorders [32][33][34][35] . In AD patients, altered GABAAR subunit regulation has been observed 36 , including decreased α1/α3 expression 37 .…”
Section: Introductionmentioning
confidence: 99%